Meta-analysis of plasma homocysteine levels in valproic acid treated patients with epilepsy - Guan-zhong NI; Jia-ming QIN; Zi-yan FANG; Yi-shu CHEN; Zi-yi CHEN; Jue-qian ZHOU; Lie-min ZHOU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Objective To determine whether valproic acid (VPA) monotherapy influences homocysteine metabolism in patients with epilepsy.  Methods Articles in English concerning the homocysteine levels in VPA monotherapeutic patients with epilepsy and published from January 1990 to August 2013 were searched through PubMed, Web of Science and EMBASE. Observational case-control studies that evaluated homocysteine levels in subjects with epilepsy compared to controls were selected. Any study lacking information regarding specific effect of VPA on homocysteine in patients with epilepsy was rejected. Definitely, non-controlled design studies, reviews, and animal or in vitro studies were also excluded. Two reviewers independently evaluated the quality of included articles and extracted the data using Newcastle-Ottawa Scale. A Meta-analysis was conducted by using Stata 12.0 software.  Results A total of 8 eligible studies were enrolled in this Meta-analysis. VPA treated patients with epilepsy (N = 266) and matched healthy controls (N = 489) were included. All included studies reached a total quality score of 6 or higher. Results of the Meta-analysis showed that plasma homocysteine levels in VPA treated patients with epilepsy was significantly higher than healthy controls under a random effect model [standardized mean difference (SMD) = 0.620, 95% CI: 0.320-0.920; P = 0.000]. There was significant heterogeneity in the estimates according to I2 test ( I2 = 65.600% , P = 0.005). Further subgroup analysis suggested that no significant difference was present when grouped by ethnicity and age, but the risk of heterogeneity in West-Asian group (I2 = 47.400%, P = 0.107) was diminished when compared with overall groups (I2 = 65.600%, P = 0.005). Sensitivity analysis was also conducted to evaluate the stability of Meta?analysis. When any single study was deleted, the corresponding pooled SMD was not substantially altered.  Conclusions VPA monotherapy is associated with the increase of plasma homocysteine levels in patients with epilepsy, and whether this association is influenced by ethnicity needs further research.   doi: 10.3969/j.issn.1672-6731.2014.12.006